Magnetooptical effects in two dimensional photonic crystals - Belotelov, V.I.; Perlo, P.; Zvezdin, A.K.; Gaponenko, N.V. (Functional Materials, 2004)
Magnetooptical properties of materials with periodically modulated dielectric constant — photonic crystals (or photonic band gap materials) have been examined with relation to their possible applications for the control of electromagnetic radiation in the integrated optics devices. For this investigation we propose the original theoretical approach based on the perturbation theory. Magnetooptical Faraday and Voigt effects have been studied near extremum points of photonic bands where their significant increase takes place. Basing on the elaborated theory, some experimental results are discussed. Experimental frequency dependence Faraday rotation angle agrees well with our theoretical predictions.